2019
DOI: 10.1111/ddi.12964
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale α‐diversity patterns in plants and ground beetles (Coleoptera: Carabidae) indicate a high biodiversity conservation value of China's restored temperate forest landscapes

Abstract: Aim: Following the near-complete destruction of China's forest ecosystems during the 20th century, recent reforestation programmes have created large-scale mosaics of protected secondary and plantation forests. These restored forests are often assumed to have limited biodiversity conservation value, but large-scale evaluations of their diversity are lacking. In our study, we compared α-diversity and species dissimilarity patterns of vascular plants and ground beetles (Coleoptera: Carabidae) in restored seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…In 150 managed forest stands across Germany, ground beetle species richness and the richness and abundance of rove beetles were positively related to overall vascular plant diversity [67]. In northeast China, positive correlations between woody plant and ground beetle species richness occurred only in mature, but not in younger secondary forests [68], highlighting that forest age and subsequent successional changes in structural properties can moderate the "enemies" hypothesis. In contrast, abundance and species richness of ground and rove beetles did not differ consistently between monocultures and two-species mixtures in plantation forests in Ireland ( [42,43], see also [69] for similar results).…”
Section: Predatory Beetlesmentioning
confidence: 97%
“…In 150 managed forest stands across Germany, ground beetle species richness and the richness and abundance of rove beetles were positively related to overall vascular plant diversity [67]. In northeast China, positive correlations between woody plant and ground beetle species richness occurred only in mature, but not in younger secondary forests [68], highlighting that forest age and subsequent successional changes in structural properties can moderate the "enemies" hypothesis. In contrast, abundance and species richness of ground and rove beetles did not differ consistently between monocultures and two-species mixtures in plantation forests in Ireland ( [42,43], see also [69] for similar results).…”
Section: Predatory Beetlesmentioning
confidence: 97%
“…The positive relationship between woody plant and ground beetle diversity found by Zou et al (2019) is limited to mature forests in a study area in temperate China. For secondary forests, no correlation was found, which the authors attributed to the lower forest age.…”
Section: Discussionmentioning
confidence: 78%
“…Nonetheless, with increasing diversity of an ecosystem, mixed results are often obtained. For example, some studies postulate positive relationships between plant diversity and ground beetles, while other studies show no or negative relationships ( Vehvilainen et al 2008 ; Worthen and Merriman 2013 ; Yeeles et al 2017 ; Zou et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that anthropogenic factors had a positive effect on tree species richness in the MTF of northeastern China (Figures 3 and 6). This finding suggests that regional afforestation and natural forest protection measures may have effectively maintained and even increased tree species diversity in this region (Zou et al, 2019).…”
Section: Discussionmentioning
confidence: 79%
“…We found that anthropogenic factors had a positive effect on tree species richness in the MTF of northeastern China (Figures 3 and 6). This finding suggests that regional afforestation and natural forest protection measures may have effectively maintained and even increased tree species diversity in this region (Zou et al, 2019). In addition, the negative effect of roadless areas on tree species richness suggests that road access can increase tree species richness by facilitating the propagation of invasive species (Joly et al, 2011; Riitters et al, 2018), and through forest management activities, including harvesting and artificial plantation of non‐native species (Bremer & Farley, 2010).…”
Section: Discussionmentioning
confidence: 92%